Burden of Anemia in Chronic Kidney Disease: A Cross-Sectional Study from the Nephrology Division, Khyber Teaching Hospital, Peshawar - Suhail, Samra; Raza, Ali; Ahmed, Annum Riaz; Khan Khalil, Rabia; Mushtaq, Wisha (Indus Journal of Bioscience Research, 2025)
Background: Chronic kidney disease (CKD) is a progressive condition commonly associated with anemia, especially in patients undergoing maintenance hemodialysis. Anemia contributes significantly to morbidity and mortality in CKD and is influenced by multiple demographic, clinical, and behavioral factors. Objective: To determine the prevalence of anemia among dialysis-dependent CKD patients at a tertiary care hospital in Pakistan and to identify key variables associated with its occurrence. Methods: A prospective, descriptive cross-sectional study was conducted from November 2024 to March 2025 at the Nephrology Unit of Khyber Teaching Hospital, Peshawar. A total of 284 adult hemodialysis-dependent CKD patients were enrolled using consecutive sampling. Data were collected via structured questionnaires and medical records. Anemia was defined as hemoglobin <12 g/dL in males and <11 g/dL in females. Results: The overall prevalence of anemia was 73.0%. Anemia was more common in females (85.6%), elderly patients (>75 years: 90%), those with diabetes (83.1%), hypertension (79.0%), lower educational levels, and longer CKD duration (>3 years: 89.8%). Conclusion: Anemia is highly prevalent among dialysis-dependent CKD patients, with specific subgroups at greater risk. Early identification and targeted management of these risk factors are crucial for improving patient outcomes.